(untitled) (Fiep Bulletin - online, 2016)
The term stress was first applied to health by Hans Selye physiologist who defined it as a state of pathogenic strain of the organism. This process sets up an important response of the body to sustain life, but at high levels can lead to serious health problems. For athletes stress is a key element in the quest for better performance and should be controlled within appropriate levels. The aim of this study was to identify the symptoms of stress pre-competitive juvenile whom were affected athletes participating in class U-15 Copa Rio International Judo For the year 2014 it was applied to “List Symptoms Stress Pre-competitive” Children and Youth - LSSPCI to a sample of 33 athletes. We observed in this study that all athletes had some level of stress, mainly psychological, demanding attention and professional support taking into consideration the risks of developing a toxic stress. We consider it essential that technicians remain attentive to levels of stress presented by their athletes, accompanying their symptoms to have it as a springboard in athletic performance, and not a risk factor for health and individual performance.